พุทธบัญญัติเกี่ยวกับนักบวชนอกศาสนา - Ācārapāli, Phramaha Prakasit (วารสารสันติศึกษาปริทรรศน์ มจร, 2018)
The objectives of this article are: 1) to study the non-Buddhist monks in Buddhist scriptures, 2) to study the the relationship between Buddhist and non-Buddhist monks, and (3) to analyze the Discipline (Vinaya) for non-Buddhist monks. This paper is a qualitative research. As a result, is was founded as follows :- 1. The non-Buddhist monk in Buddhist scriptures was called Aññatitthiya classified into three groups, namely, 1) ascetic (Isi or Jatila ), 2) Parippãjaka divided into 2 groups; ascetics wearing clothes and nude ascetics (whereas nude ascetics are divided into Acelaka and Ājĩvaka), and 3) Nigantha (followers of Maha Veera). These other religious ascetics often lived together in a hermitage or monastery which is similar to a Buddhist temple. 2. In term of relationship, Buddhism had dealt with other religious ascetics in three dimensions, namely, 1) personal relationship, 2) social relationship, and 3) teaching relationship. Some teachings are identical to each others. This identity of teaching generates admiration to one another. Although there were some different teachings, they were based on good intention to make correct understanding without quarrels. 3. The discipline legislated by the Buddha for non-Buddhist monks was classified into six topics, namely, 1) legislation on ordaining The non-Buddhist monks, 2) legislation on treatment towards monks who convert to other religions, 3) legislation on practice teachings of non-Buddhist monks, 4) legislation on the use of four requisites, 5) legislation on aid non-Buddhist monks, and 6) legislation on behavior as non-Buddhist monks. These Buddhist legislations were legislated by Buddha in order to prevent suspicion among religions and infiltration to undermine Buddhism as well as confusion among Buddhists. However, Buddha did not prohibit anyone who demanded to study Buddhism with good faith.